Genomic and transcriptomic heterogeneity of colorectal tumours arising in Lynch syndrome1. Issue 2 (5th September 2017) - Binder, Hans; Hopp, Lydia; Schweiger, Michal R; Hoffmann, Steve; Jühling, Frank; Kerick, Martin; Timmermann, Bernd; Siebert, Susann; Grimm, Christina; Nersisyan, Lilit; Arakelyan, Arsen; Herberg, Maria; et al.
Abstract: Colorectal cancer (CRC) arising in Lynch syndrome (LS) comprises tumours with constitutional mutations in DNA mismatch repair genes. There is still a lack of whole‐genome and transcriptome studies of LS‐CRC to address questions about similarities and differences in mutation and gene expression characteristics between LS‐CRC and sporadic CRC, about the molecular heterogeneity of LS‐CRC, and about specific mechanisms of LS‐CRC genesis linked to dysfunctional mismatch repair in LS colonic mucosa and the possible role of immune editing. Here, we provide a first molecular characterization of LS tumours and of matched tumour‐distant reference colonic mucosa based on whole‐genome DNA‐sequencing and RNA‐sequencing analyses. Our data support two subgroups of LS‐CRCs, G1 and G2, whereby G1 tumours show a higher number of somatic mutations, a higher amount of microsatellite slippage, and a different mutation spectrum. The gene expression phenotypes support this difference. Reference mucosa of G1 shows a strong immune response associated with the expression of HLA and immune checkpoint genes and the invasion of CD4+ T cells. Such an immune response is not observed in LS tumours, G2 reference and normal (non‐Lynch) mucosa, and sporadic CRC. We hypothesize that G1 tumours are edited for escape from a highly immunogenic microenvironment via loss of HLA presentation and T‐cell exhaustion. In contrast, G2 tumours seem to develop in a less immunogenic microenvironment where tumour‐promoting inflammation parallels tumourigenesis. Larger studies on non‐neoplastic mucosa tissue of mutation carriers are required to better understand the early phases of emerging tumours. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.